Hydrogen Gas Production in a Stand-Alone Wind Farm - Naziry Kordkandy, M.; Arash, A.; Nazary Kordkandy, M. (Engineering, Technology & Applied Science Research, 2017)
This paper is analyzing the operation of a stand-alone wind farm with variable speed turbines, permanent magnet synchronous generators (PMSG) and a system for converting wind energy during wind speed variations. On this paper, the design and modeling of a wind system which uses PMSG’s to provide the required power of a hydrogen gas electrolyzer system, is discussed. This wind farm consists of three wind turbines, boost DC-DC converters, diode full bridge rectifiers, permanent magnet synchronous generators, MPPT control and a hydrogen gas electrolyzer system. The MPPT controller based on fuzzy logic is designed to adjust the duty ratio of the boost DC-DC converters to absorb maximum power. The proposed fuzzy logic controller assimilates, with (PSF) MPPT algorithm which generally used to absorb maximum power from paralleled wind turbines and stores it in form of hydrogen gas. The system is modeled and its behavior is studied using the MATLAB software.